INFLUENCE OF WORKING CAPITAL MANAGEMENT AND POLICY TO PROFITABILITY OF RETAIL TRADING SECTOR IN INDONESIA - Tjandra, Eric
Wholesale and retail trade is an important sector in the economy of Indonesia contributing around 13% of Gross Domestic Product (GDP). In 2020, GDP of wholesale and retail trade sector contracted by 3.7% due to COVID-19 leading to mobility restrictions. From 2020 up until the writing of this report, new COVID-19 variants are emerging and mobility restrictions are regularly tightened and loosened. This led Indonesia to be hit by a ‘Tsunami of Bankruptcy’ indicated by mall closures, malls put for sale and supermarket closures, amongst others. Bankruptcy is ultimately led by the inability to meet short-term obligations. Working Capital (WC) Management and Policy (WCMP) concerns financial decision on a short-term perspective, typically less than a year. Firms need to survive in the short-term in order to strive in the long-term. This research aims to examine the influence of WCMP to profitability on Indonesian public listed firms in the retail trading subsector during 2011-2020. WCMP is important to different types of sector and firm size but it could be more critical in certain sectors, such as the retail trading sector. Retail trading sector is a WC-intensive sector where receivables, payables, and inventory make up a significant portion of the statement of financial position. In this research, WC Management (WCM) is measured by the Cash Conversion Cycle (CCC) which comprises Days Sales Outstanding (DSO), Days Inventory Outstanding, and Days Payable Outstanding (DPO); WC Policy is measured current assets divided by total assets or referred to as WC Investment Policy (WCIP) and current liabilities divided by total assets or referred to as WC Financing Policy (WCFP); and profitability is measured by Earnings Before Interest, Tax, Depreciation, and Amortization Margin (EBITDAM). The panel data regression shows negative and significant influence of CCC, DIO, and WCFP to EBITDAM; negative but insignificant influence of DSO to EBITDAM; and positive and significant influence of DPO and WCIP to EBITDAM. This means that managers of retail trading sector firms may formulate and implement strategies to shorten CCC by focusing on increasing inventory turnover and extending payments to suppliers with an objective to improve EBITDAM. Retail trading sector firms will also have its EBITDAM affected positively by adopting a conservative WC Policy instead of an aggressive one which means having higher current assets and lower current liabilities with respect to total assets.